Azatriphenylene-based D-A-D-typed hole-transporting materials for perovskite solar cells with tunable energy levels and high mobility. (August 2021) - Sun, Zhu-Zhu; Feng, Shuai; Ding, Wei-Lu; Peng, Xing-Liang; Liu, Jing-Lun; Xu, Xing-Lei
Graphical abstract: Nine D-A-D-typed HTMs are constructed based on the electron-deficient moieties of diazatriphenylene (DAT), tetraazatriphenylene (TAT) and hexaazatriphenylene (HAT), and their influences on electronic, optical and charge transport properties of HTMs are evaluated by performing quantum chemical calculations. Highlights: Nine azatriphenylene-based D-A-D-typed HTMs are designed. Performance of HTMs is tuned by tailoring of acceptor group. New HTMs display down-shifted HOMO levels and red-shifted spectra. Good molecular planarity is favorable to improve hole mobility of HTMs. Abstract: Computational study on relationship between molecular structure and property of small molecule hole-transporting materials (HTMs) is an efficient pathway to acquire potential HTMs for perovskite solar cells (PSCs). Herein, by conjugating the acceptor groups of electron-deficient diazatriphenylene (DAT), tetraazatriphenylene (TAT) and hexaazatriphenylene (HAT), and p -methoxy-substituted triphenylamine (MeOTPA) electron-donors, six novel donor–acceptor-donor (D-A-D) typed HTMs (SM11 ~ SM16) are designed. Furthermore, three thiophene-substituted acceptors (SM17 ~ SM19) are also investigated. The influences of acceptor moiety on the performance of HTMs are studied by carrying out theoretical chemical calculations. Compared with the reported HTM with triphenylene unit (TPH-T), the new tailored HTMs (SM11 ~ SM19) exhibit more negative highest occupied molecular orbital (HOMO) energy levels and slightly red-shifted light absorption due to the increased electron-deficient property of acceptor group and linked positions with the MeOTPA-donor. Meanwhile, our results show that the small torsion angle between the acceptor and the donor is beneficial to promote the hole transport in HTMs, and the thiophene units on acceptor may also be helpful to enhance the charge mobility of HTMs. In addition, the large charge transfer amounts and small exciton binding energies are found for designed HTMs, which will be favorable to facilitate the electron-hole separation in HTMs. The stability of HTMs may be decreased based on the calculated results of electrostatic surface potential and absolute hardness. We hope this work could highlight the potential of azatriphenylene acceptor-based D-A-D typed HTMs for efficient PSCs.